A behavior-based pricing model in retail systems considering vertical and horizontal competition. (February 2021) - Ziari, Matineh; Sajadieh, Mohsen S.
Highlights: Competitive pricing model with behavior-based demand is proposed in retail system. Horizontal competition is conserved among wholesalers and retailers, individually. Stackleberg game is used for uncooperative vertical competition in bi-level form. Behavior-based price discrimination is used to find the lower-level equilibriums. Abstract: Demand fluctuations, price of products and customer's preferences play an important role in distribution and retail systems. In this paper, the issue of competitive pricing is investigated in a distribution system considering customers' behavior. The distribution system includes two wholesalers and two retailers with asymmetric power in the market. A new bi-level model is proposed to demonstrate the Stackelberg competition among the main entities in distribution systems (wholesalers and retailers). Moreover, the horizontal competition is examined among the retailers and wholesalers, individually. The horizontal competition among retailers is investigated on retail price and retailers' location using Behavior-Based Price Discrimination (BBPD). On the other hand, the competition among wholesalers is modeled on wholesale price and service level. The proposed model concentrates on profit maximization objective for the entities and utility maximization for the customers through behavior-based price discrimination. The model is carried on an industrial case problem for sensitivity analysis and comparison of different scenarios to derive managerial insights.